Determination of Herbicide Diuron levels in palm oil matrices using HPLC-UV - Mohd. Izwarie Ramli,; Zuriati Zakaria,; Ismail Sahid,; Tan, Yew Ai; Halimah Muhamad, (Universiti Kebangsaan Malaysia, 2012)
The objective of this study was to develop a method for the determination of diuron (3-(3,4-dichlorophenyl)-1,1-dimethyl urea) residue in crude palm oil (CPO) and crude palm kernel oil (CPKO) matrices. The method involves the extraction of the herbicide from the oil matrix using low temperature precipitation and solid phase extraction techniques, detected by high performance liquid chromatography-ultra violet (HPLC-UV). The HPLC separation was carried out on an AscentisTM RP-Amide column and elution with acetonitrile (solvent A) and water-methanol (2:1, v/v) (solvent B) as a suitable solvent system, at ratio of 4:6 (v/v). The optimum volume of acetonitrile for the extraction of diuron was 30 mL and 4 mL was obtained as the optimum volume of the solvent for elution analyte through the SPE cartridge. A linear correlation was obtained for the concentration of diuron from 0.05–1.0 μg mL-1 with a correlation coefficient of 0.99. The recovery of diuron from CPO was 83.2–101.4% with a relative standard deviation of 1.4–9.9% and 79.4–87.9% with relative standard deviation of 0.9–5.6% for CPKO. The method detection limit and limit of quantification obtained were 0.018 μg g-1 and 0.058 μg g-1, respectively. The method was used to determine diuron residues in palm oil from different refineries situated at different locations throughout Malaysia